Recurrent Dystonic Crisis and Rhabdomyolysis Treated with Dantrolene in Two Patients with Aromatic L-Amino Acid Decarboxylase Deficiency - Micallef, J.; Stockler-Ipsiroglu, S.; van Karnebeek, C.D.; Salvarinova-Zivkovic, R.; Horvath, G. (Neuropediatrics, 2020)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare, autosomal recessive inborn error of metabolism in which several neurotransmitters including serotonin, dopamine, norepinephrine and epinephrine are deficient. Symptoms typically appear in the first year of life and include oculogyric crises and dystonia, hypotonia, and global developmental delay. Dystonia is of particular concern as a dystonic storm can ensue leading to rhabdomyolysis. Rhabdomyolysis can become life-threating and therefore its recognition and prompt management is of significant importance. Here we present two cases of patients with AADC deficiency and a history of dystonic crisis causing rhabdomyolysis. We hypothesize that in addition to the hypodopaminergic, a hypercholinergic state is contributing to the pathophysiology of dystonia in AADC deficiency, as well as to the associated rhabdomyolysis. We were able to prevent rhabdomyolysis in both patients with using Dantrolene and we suggest using a trial of this medication in cases of sustained dystonic crisis in AADC deficiency patients.
Keywords: aromatic L-amino acid decarboxylase (AADC) deficiency; dystonic crisis; rhabdomyolysis; dopamine deficiency; cholinergic crisis